Comparison of intubating conditions during rapid tracheal intubation between Rocuronium and combination of Rocuronium with Vecuronium - Piya, Roshan (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Rapid sequence induction (RSI) is usually indicated during emergency surgical procedure in the presence of full stomach and other conditions with an increased risk of aspiration. The use of succinylcholine has been the gold standard for RSI because of its rapid onset and short duration of action in spite of its adverse effects and contraindications in many conditions. Because of these side effects of succinylcholine many techniques have been attempted and published to replace succinylcholine when it is contraindicated. Aim of the study was to compare the quality of intubation conditions during tracheal intubation in 60 seconds after administration of thrice ED95 dose (0.9mg/kg) of rocuronium and combination of one & half times ED95 dose (0.45mg/kg) of rocuronium and one & half times ED95 dose (0.075mg/kg) of vecuronium.Methods: Sixty patients scheduled for elective surgery requiring tracheal intubation, age ranges from 18- 65 years were chosen after informed consent. Prospective, Randomized, double blind study was conducted in the Department of Anaesthesiology, Tribhuvan University Teaching Hospital.Results: The intubating conditions obtained with the combination groups were comparable with that of rocuronium alone. Most of the patients had excellent intubating condition and few had good intubating condition. The combination of one & half ED95 dose of rocuronium & one & half ED95 dose of vecuronium produced either excellent or good intubating condition during RSI.Conclusion: Thus the combination of this drug with above dose can be an alternative to succinylcholine and rocuronium for RSI.